Persepsi nelayan terhadap penangkapan ikan terukur ditinjau dari aspek sosial ekonomi dan lingkungan - Poltak, Hendra; Handayani; Muhfizar; Ndahwali, Daniel Heintje; Gunaisah, Endang; Karubaba, Oktovianus Cristian; Purnomo, Adi (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to understand the perceptions of fishermen towards the regulated fishing policy implemented by the Indonesian government. This policy is an effort to maintain the sustainability of fishery resources and marine ecosystems. The research method used is a quantitative survey with a descriptive approach, conducted on fishermen in the Sorong Manoi District, West Papua. Data were collected through questionnaires, structured interviews, and field observations, with a sample of 72 fishermen. The results of the study show that most fishermen have a positive understanding of this policy, recognizing its benefits in maintaining the sustainability of fish resources and reducing conflicts among fishermen. However, there are concerns related to the short-term economic impact and the need for more effective socialization and technical assistance. Fishermen also realize the importance of maintaining the marine ecosystem and support the use of environmentally friendly fishing gear.